Organized crime and corruption across borders: exploring the belt and road initiative - Lo, Tit Wing; Siegel, Dina; Kwok, Sharon Ingrid (Routledge studies in crime and justice in Asia and the Global South, 2020)
"Bringing together experts across the Global South and Europe, this book considers transnational organized crime and corruption across One Belt One Road (OBOR). It examines crime and corruption in China and its international united front tactic; analyses various forms of transnational organized crime such as trafficking of illegal drugs, looted antiquities, and wildlife and counterfeit products; and presents studies on corruption and organised crime in selected OBOR countries including Russia, Kazakhstan, Lithuania, Czech Republic, Poland, and Bangladesh. This book makes a significant contribution to the development of Southern Criminology and will also be of interest to those engaged with transnational organized crime, political economy, international relations, and Asian and Chinese studies"--